Identifikasi Tomato infectious chlorosis virus dan Tomato chlorosis virus melalui Reverse Transcription Polymerase Chain Reaction dan Analisis Sikuen Nukleotida - Sari Nurulita; Gede Suastika (Jurnal Fitopatologi Indonesia, 2013)
Tomato chlorosis disease was found more frequent on production area in West Java recently. Observation in the field showed typical symptoms of Tomato infectious chlorosis virus (TICV) and Tomato chlorosis virus (ToCV). The objective of this research is to identify TICV and ToCV associated with chlorosis disease on tomato plants in West Java (Cipanas, Lembang and Garut) using reverse transcription polymerase chain reaction (RT-PCR) method and nucleotide sequence analysis. DNA target of 417 bp and 360 bp was successfully amplified only from Cipanas sample using specific primers, TICV-CF/TICV-CR and ToCV-CF/ToCV-CR, respectively. Sequence analysis confirmed that chlorosis disease in Cipanas was associated with TICV and ToCV infection. Nucleotide sequence and phylogenetic analysis showed that TICV from Cipanas has high homology to and belongs to the same group with TICV from Japan and Spain; whereas ToCV from Cipanas has high homology to and belongs to the same group with ToCV from America.